From Pelvis to Foot: A Functional Approach to Preventing Ankle Sprains in Athletes - Gabriel Quintero (Journal of Sports and Exercise Medicine, 2026)
Background Ankle sprains are among the most common injuries in sports, often characterized by high recurrence rates despite appropriate local treatment. Traditional approaches primarily focus on the injured joint, with limited attention to proximal biomechanical factors that may predispose athletes to injury. Objective To propose a functional, longitudinal kinetic chain model in which sacroiliac joint dysfunction may act as a predisposing factor for ankle sprain/strain injuries in athletes. Methods This paper presents a clinical hypothesis based on biomechanical reasoning and observational findings. The proposed model describes how sacroiliac joint dysfunction, particularly posterior innominate rotation (PI), may lead to pelvic obliquity and functional leg length discrepancy. These changes may induce compensatory femoral external rotation and foot toe-out, altering ground contact mechanics during gait and running. Results (Hypothesis) The altered alignment and loading pattern may increase the vertical impact force and modify the ground reaction vector on the functionally shorter limb, resulting in reduced mechanical stability at the ankle during heel strike or foot contact. Over time, this may increase susceptibility to inversion or eversion injuries, manifesting clinically as recurrent sprain/strain. Conclusion Ankle sprains in athletes may, in some cases, represent the distal expression of a proximal biomechanical imbalance. Incorporating assessment of the sacroiliac joint and the longitudinal kinetic chain into routine clinical evaluation may improve injury risk identification and contribute to more effective prevention strategies. Further research is needed to investigate this proposed relationship.
Keywords: sacroiliac joint dysfunction